2021
DOI: 10.30519/ahtr.784232
|View full text |Cite
|
Sign up to set email alerts
|

How Delightful is Indian Wellness Tourism? A Netnographic Study

Abstract: The growing number of wellness care facilities in India has raised concern over the service quality that is being provided to the tourists. This research targets to explore the dimensions of wellness tourism service quality based on customers' quality perception. Social media platforms such as Google reviews and hotel review blogs/websites were used to gather 400 public reviews. A Naïve Bayes machine learning Sentiment Analysis approach was used to identify critical areas to improve service delivery, customer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Rodrigues et al (2020) emphasize that in Hotel Spas in Portugal the factors that positively influence guest satisfaction are rooms, nature, food, location and value for money. Additionally, a growing number of international contributions from China, Canada and India highlight the role of food in the holistic wellness products offered by Spa Retreats (Kim and Yang, 2021;Mishra and Panda, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Rodrigues et al (2020) emphasize that in Hotel Spas in Portugal the factors that positively influence guest satisfaction are rooms, nature, food, location and value for money. Additionally, a growing number of international contributions from China, Canada and India highlight the role of food in the holistic wellness products offered by Spa Retreats (Kim and Yang, 2021;Mishra and Panda, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Chittiprolu et al (2021) reviewed online hotel reviews by using unsupervised text mining techniques, and results put forth that satisfied customers mention tangible features, whereas dissatisfied customers complain about intangible service problems. Likewise, Mishra and Panda (2021) reviewed wellness facility reviews, and tangibility was found to be the most important dimension.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed ensemble classifier and deep learning models provide better classification accuracy Chittiprolu et al (2021) To comprehend the dimensions of service appreciation and complaints by comparing positive and negative reviews Satisfied customers mentioned about tangible features of the hotel stay, whereas complaints are about intangible service problems Mishra and Panda (2021) To explore the service quality dimensions of wellness tourism industry based on customers' quality perception Tangibility was found to be the most important dimension followed by empathy, assurance, reliability and responsiveness Complaint Management Focus Ravi et al (2017) To propose a hybrid complaint analytics model based on fuzzy formal concept analysis and sentiment analysis With the proposed model, complaints can be ranked and visualized according to the negative sentiment score Leem and Eum (2021) To propose a method of measuring service quality and detecting complaints through analysis of customer online reviews…”
Section: Social Listening Focusmentioning
confidence: 99%
“…From the explanation above, it can be seen that the highest number of questions received by AHRC in 2015-2016 were two matters, namely disability discrimination and racial discrimination. (Mishra & Panda, 2021) The number of questions related to racial discrimination in 2015-2016 was 21% of the 16,836 questions. This means that there were 3,535 questions submitted regarding racial discrimination.…”
Section: Accommodation and Investigation Of Public Complaints By Ahrcmentioning
confidence: 99%